2014
DOI: 10.1002/cne.23565
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal lateral geniculate nucleus and optic chiasm in human albinism

Abstract: Our objective was to measure how the misrouting of retinal ganglion cell (RGC) fibers affects the organization of the optic chiasm and lateral geniculate nuclei (LGN) in human albinism. We compared the chiasmal structures and the LGN in both pigmented controls and patients with albinism by using high-resolution structural magnetic resonance imaging (MRI). We studied 12 patients with oculocutaneous albinism and 12 age-matched pigmented controls. Using a 3T MRI scanner, we acquired a T1 -weighted three-dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 36 publications
4
24
1
3
Order By: Relevance
“…The post orbital visual pathway was studied using high‐resolution T1‐weighted MRI imaging to measure cisternal optic nerves, chiasm, optic tracts and V1 cortical thickness. Our aim was to confirm previous reports regarding altered morphology of these structures in PWA (Schmitz et al, ; Bridge et al, ; Mcketton et al, ).…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…The post orbital visual pathway was studied using high‐resolution T1‐weighted MRI imaging to measure cisternal optic nerves, chiasm, optic tracts and V1 cortical thickness. Our aim was to confirm previous reports regarding altered morphology of these structures in PWA (Schmitz et al, ; Bridge et al, ; Mcketton et al, ).…”
Section: Introductionsupporting
confidence: 71%
“…It had been hypothesised by the authors of these earlier studies that the finding of smaller optic nerves, chiasm and tract in albinism could be due to the underdevelopment of the fovea (Von dem Hagen et al, ; Mcketton et al, ). Although we did not see any relationship between foveal development and the physical size of the chiasm, our DTI data shows significant relationship between foveal development and number of streamlines crossing the chiasm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 These anomalies are likely to be the direct result of decreased ganglion cell numbers in the central retina in albino patients. 33,34 In the present study, the OCT findings showed a significant reduction in the GCC thickness in the temporal parafovea in patients with foveal hypoplasia. In general, the development of the foveal pit occurs from 24 weeks of gestation and reaches adult conformation by 15 months postpartum.…”
Section: Discussionmentioning
confidence: 63%
“…5,30 Many other morphologic anomalies have been reported in the visual pathway of patients with albinism, such as reduced central retinal ganglion cell (RGC) numbers, 31 optic nerves and chiasms of smaller diameter, 32 and decreased lateral geniculate nuclei numbers 33 and gray matter volume at the occipital cortex. 34 These anomalies are likely to be the direct result of decreased ganglion cell numbers in the central retina in albino patients.…”
Section: Discussionmentioning
confidence: 99%